Higher Education Students and Entrepreneurial Attitudes: A Human Resource Approach - Sadikin, Mochamad Rizki; Junaedi, Juanedi; Azis, Husni; Setyaningrum, Retno (Jurnal Entrepreneur dan Entrepreneurship, 2022)
This paper is to perform analyze of the influence of entrepreneurial education, locus of control and self eficacy on entrepeneurial attitude among students. The population of this study are the class of 2015 managament students Economics Faculty of Mercu Buana University. Total sample used is 147 out of 233 total population. Data collection used a survey method, with the questionnaire research intrument. It used a Partial Least Square aplication in analysing the data. The result proves that entrepreneurial education has a positive influence on entrepreneurial attitudes, locus of control has a positive influence on entrepreneurial attitudes and self efficacy has a positive influence on enterepeneurial attitudes. Entrepreneurship education has a positive effect on entrepreneurial attitudes among students. When students are given more subjects regarding entrepreneur issues it sparks their will to start a self owned small campany. Secondly, the internal locus of control has a positive and significant influence on entrepreneurial attitudes. Students with higher internal locus of control have confident to control and manage their own business. They believe their business will success within their control and ability. Lastly, self-efficacy has a positive and significant effect on entrepreneurial attitudes. Higher self-efficacy student means feels confident that they will be able to learn and do well as an entrepreneur